CLINICAL ASSOCIATION OF SERUM MAGNESIUM AND SERUM FIBRINOGEN LEVELS WITH ACUTE EXACERBATION OF CHRONIC OBSTRUCTIVE PULMONARY DISEASE- A PROSPECTIVE OBSERVATIONAL STUDY - A, Niventhi; D, Praveen; M, Vijey Aanandhi (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Acute exacerbations (AE) are a contributing cause of worsening chronic obstructive pulmonary disease (COPD) in conditions of lung function decline, quality of liveliness, and natural selection. The most important concept of this article is the positive correlation between the serum magnesium levels at worsening of symptoms and annual number of episodes. Methods: Blood samples from the patients who are diagnosed with AE of COPD will be collected and evaluated for serum magnesium levels and serum fibrinogen levels. Low serum magnesium is a modifiable risk factor. It is generally believed that, due to its bronchodilating effect, a decreased level of magnesium increases COPD exacerbations. The best blood biomarker for the systemic tenderness in COPD used here is plasma fibrinogen. Those with the increased fibrinogen levels had induced the higher admission rates with COPD. This clause deals with the association of both serum magnesium and serum fibrinogen levels with AE-COPD. Results: The serum magnesium levels on discharge in stable type were found to be 2.3±0.27, and in exacerbation, it was found to be 1.56±0.37. Moreover, on discharge, serum fibrinogen levels in stable type were found to be 1.64±0.32, and in exacerbation, it was found to be 2.18±0.40. Conclusion: Low serum magnesium levels may be a complication for AE of COPD. High serum fibrinogen levels may be a complication for AE of COPD. We hereby recommend regular screening of serum magnesium and serum fibrinogen levels for all the COPD patients to predict and prevent AE.